Does green stem photosynthesis affect plant drought tolerance and recovery in avocado? - Valverdi, Nadia Antonella; Guzmán-Delgado, Paula; Goldsmith, Gregory R.; Ávila‐Lovera, Eleinis (Oxford University Press, 2026)
Woody plants with green stems may have advantages over non-green-stemmed plants in that extra photosynthetic carbon gain has the potential to improve plant drought tolerance and aid drought recovery. However, most studies relating to green stem photosynthesis and drought tolerance have been conducted on non-horticultural plants under natural growing conditions. We investigated whether avocado green stem photosynthesis enhances drought tolerance and recovery. We applied light exclusion and drought treatments to 3-year-old potted trees of cultivars ‘Hass’ and ‘Fuerte’. Measurements of soil moisture, midday stem water potential, stem photosynthesis, bark chlorophyll concentration, concentration of sugars + starch and stem hydraulic conductivity were conducted before, during, and 3 weeks after rewatering. Green stems of avocado re-assimilate CO2, but values did not significantly differ between cultivars. We also found that light exclusion reduced stem photosynthesis by 65% in ‘Fuerte’ and 30% in ‘Hass’ although bark chlorophyll concentration was unchanged. Drought reduced stem photosynthesis by 60%. Following drought recovery, there were neither treatment nor cultivar effects on stem photosynthesis. We also observed no effect of light treatment on hydraulic conductivity, such that there is no clear effect of stem photosynthesis on drought tolerance of these avocado trees. However, we observed an increase in hydraulic conductivity during the drought period with an increase in the concentration of sugars in the sapwood and a decrease in the concentration of starch, suggesting osmotic adjustment. Nonetheless, the contribution of carbon gain through stem photosynthesis may not play a significant role in hydraulic functioning of avocado under these conditions.